What motivates stakeholders to engage in collaborative innovation in the infrastructure megaprojects? - Chen, Xiaoyan; He, Qinghua; Zhang, Xinyue; Cao, Tingting; Liu, Yan (Journal of Civil Engineering and Management, 2021)
Collaborative innovation has become an innovation paradigm to improve innovation performance and firms’ economic output. However, there is relatively little research investigating stakeholders’ drivers for engaging in collaborative innovation and the relative importance of drivers in infrastructure megaprojects. This research aims to address this gap by identifying the drivers for collaborative innovation and their relative importance in the context of infrastructure megaprojects. We adopt the literature review and questionnaire survey methods to identify drivers, the Relative Importance Index to rank them, and exploratory factor analysis to group them. The results show that 18 drivers are grouped into 6 dimensions. Their rankings are as follows: responding to project and clients’ requirements, improving efficiency, gaining rewards, learning, responding to competition, responding to environmental changes. The research contributes to stakeholders’ drivers to engage in collaborative innovation and the relative importance of drivers in the context of infrastructure megaprojects. Identifying and prioritizing stakeholders’ drivers can provide practitioners with suggestions on managing the collaborative innovation process in infrastructure megaprojects.